Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 2329358 species occurrences available in GBIF matching the query: { "PublishingCountry" : [ "is Colombia" ] } The dataset includes 2329358 records from 245 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003626-160509122628363/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences